Trace - Cummings, Pat (Harper, 2020)
Trace Carter is still feeling out of place at his new home in his Auntie Lea's brownstone in New York, trying to forget the terrible accident that killed his parents, when one day he takes a wrong turn in the Public Library only to run into a crying little boy with tattered old clothes, who seems to be a ghost. Trace discovers the ghost has ties to his own history, and the accident, and that if he learns what the ghost boy knows he may finally be able to move on himself.